Indicadores de sustentabilidade para aplicação no processo de desenvolvimento de produtos na indústria de autopeças - Ussui, Paulo Roberto Savelli (2013)
The severe environmental degradation caused by human activities in recent decades has forced organizations to take actions and measures in order to reduce or eliminate the negative effects caused by industrial activities. In this sense, sustainability indicators have grown in importance because they allow to assess the level of sustainability from various entities, identifying potential for improvement and progress achieved. Despite the great variety of existing indicators, there are still unexplored areas, such as indicators for product development in the auto parts industry. Aiming to contribute to the creation of more sustainable products, guiding the development process since the earliest stages, it was proposed in this work a set of sustainability indicators, divided into product indicators and design indicators. These two sets of indicators were defined based on the study of best practices and recommendations from various techniques such as design for environment and sustainability, study of existing sustainability indicators and the needs of the automotive industry. The result was a set of 23 product indicators, evaluating the product characteristics in a quantitatively way, and 26 design indicators, assessing whether the main aspects and techniques of design for sustainability are being considered throughout the development process, in a qualitative way. In order to demonstrate the application and use of the proposed indicators, it was presented an example, based on the development of a new component for diesel engines, starting from strategic planning to the product discontinuation from the market. The example showed that the defined indicators are very useful in guiding the development team to achieve a sustainable product, based on the goals defined at the beginning of the project, which can be incorporated into the development process for automotive companies.